ASAS ITIKAD BAIK DALAM PERJANJIAN PENDAHULUAN (VOOR OVEREENKOMST) PADA PERJANJIAN PENGIKATAN JUAL BELI RUMAH (STUDI PUTUSAN PENGADILAN NEGERI SIMALUNGUN NO 37/PDT/PLW/2012/SIM) - Novalia Arnita Simamora; Tan Kamello; Rosnidar Sembiring; Jelly Leviza (Universitas Sumatera Utara, 2015)
ABSTRACT PPJB (purchase contract) on housing is a preliminary agreement (voor overeenkomst) between a seller and a potential buyer as it is stipulated in Article 42, paragraph 1 of Law No. 1/2011 on Housing and Residence and in Kemenpera (the Decree of the Minister of Low-Cost Housing) No. 9/1995 which become the basis for PPJB as the preliminary agreement. Even though PPJB is consensual, it is made by paying attention to good faith principle as it is stipulated in Article 1338, paragraph 3 of the Civil Code. The party with good faith is given legal protection as it is stipulated in the Jurisprudence of the Supreme Court of the Republic of Indonesia No. 251k/sip/1958. Therefore, this thesis attempted to analyze the legal consequence of PPJB made by PT Surya C in the perspectives of good faith and legal protection for potential buyers who had good faith. Keywords: Good Faith Principle, Preliminary Agreement, PPJB (Purchase Contract) in Housing